2021
DOI: 10.1192/bji.2021.13
|View full text |Cite
|
Sign up to set email alerts
|

Suicide among Ugandan university students: evidence from media reports for 2010–2020

Abstract: University students are in transition to adulthood and face multiple challenges that may lead to suicide. They are reported to have a higher risk of suicide by the World Health Organization. As there is no national suicide database in Uganda, we analysed student suicide using the press/media reports of suicides published between 2010 and 2020. A total of deaths by 23 suicide were identified: 19 were males, relationship problems were the main suicide reason (n = 6) and hanging was the most frequently used suici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 13 publications
3
29
0
Order By: Relevance
“…36 Furthermore, several studies observe the diversity of suicide and suicidal behaviors across gender, including attributing factors such as social construction of masculinity and femininity, life historyrelated issues, lifestyle and social status conditions, their role in society, and psychological vulnerabilities. [37][38][39][40] Consistent with this scenario, all the prior studies conducted during the pandemic reported females were at higher risk of suicidal ideation [21][22][23][24] and other mental health problems, 41,42 but no gender-based statistical difference was found in this study. Such an unexpected finding needs to be explored in future studies considering a greater focus on gender-based vulnerabilities towards suicide.…”
Section: Discussionsupporting
confidence: 84%
“…36 Furthermore, several studies observe the diversity of suicide and suicidal behaviors across gender, including attributing factors such as social construction of masculinity and femininity, life historyrelated issues, lifestyle and social status conditions, their role in society, and psychological vulnerabilities. [37][38][39][40] Consistent with this scenario, all the prior studies conducted during the pandemic reported females were at higher risk of suicidal ideation [21][22][23][24] and other mental health problems, 41,42 but no gender-based statistical difference was found in this study. Such an unexpected finding needs to be explored in future studies considering a greater focus on gender-based vulnerabilities towards suicide.…”
Section: Discussionsupporting
confidence: 84%
“…Six have been in Uganda and one in Rwanda, leaving out other highly affected countries in the region like Kenya. In addition, a recent publication by Kaggwa et al (2021) reported 5 out of 21 university students allegedly died by suicide after using money meant for university tuition fees on gambling [ 14 ]. Therefore, gambling-related suicide may be a concern among youths in the East Africa region.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In Uganda, evidence suggests that problem gambling is associated with mental health problems such as depression, anxiety, and suicidality [ 13 ]. Another study in Uganda reported 21 cases of suicide among university students, five of which were gambling-related [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…University education is an intrinsically demanding time in many students’ lives[ 4 – 6 ]. There are several demands on a student’s time including course work, relationships, examinations, part-time work, internship, pressure from parents and guardians, and practical/ward work for medical students [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%